Challenges in closing the gap between software and hardware in robotics - Mohamed Bader El-Den; Ahmed Hebala (Robotics: Integration, Manufacturing and Control, 2024)
The integration of sophisticated software into robotics, especially with the emergence of generative AI and other AI technologies, marks an important step in the domain of automation and intelligent systems. As robotic systems become increasingly complex, there is a growing demand for advanced AI-driven software solutions that can ensure efficient and seamless operations. This paper explores some of the challenges in the integration of software and robotics, such as interoperability, real-time processing, and user-centric design, and proposes AI-centric strategies to address these challenges.